Genomics and Pathways Involved in Maize Resistance to Fusarium Ear Rot and Kernel Contamination With Fumonisins - Cao, Ana; de la Fuente, María; Gesteiro, Noemi; Santiago, Rogelio; Malvar, Rosa Ana; Butrón, Ana (Frontiers in Plant Science, 2022)
Fusarium verticillioides is the causal agent of maize ear rot and produces fumonisins, which are mycotoxins that are toxic to animals and humans. In this study, quantitative trait loci (QTL) and bulk-segregant RNA-seq approaches were used to uncover genomic regions and pathways involved in resistance to Fusarium ear rot (FER) and to fumonisins accumulation in maize kernels. Genomic regions at bins 4.07–4.10, 6.00–6.01, 6.04–6.05, and 8.05–8.08 were related to FER resistance and/or reduced fumonisins levels in kernels. Comparison of transcriptomes between resistant and susceptible inbred bulks at 10 days after inoculation with F. verticillioides revealed 364 differentially expressed genes (DEGs). In resistant inbred bulks, genes involved in sink metabolic processes such as fatty acid and starch biosynthesis were downregulated, as well as those involved in phytosulfokine signaling and many other genes involved in cell division; while genes involved in secondary metabolism and compounds/processes related to resistance were upregulated, especially those related to cell wall biosynthesis/rearrangement and flavonoid biosynthesis. These trends are indicative of a growth–defense trade-off. Among the DEGs, Zm00001d053603, Zm00001d035562, Zm00001d037810, Zm00001d037921, and Zm00001d010840 were polymorphic between resistant and susceptible bulks; were located within the confidence intervals of detected QTL; and showed large differences in transcript levels between the resistant and susceptible bulks. Thus, they were identified as candidate genes involved in resistance to FER and/or reduced fumonisins accumulation.